Factors Affecting Service Marketing Strategy in Hospital: A Narrative Review - Ika Sulistyaningrum Hapsari; Sutopo Patria Jati; Septo Pawelas Arso (Universitas Aisyah Pringsewu, 2021)
Health services marketing is an integrated strategy that comprises of marketing concepts based on scientific techniques that primarily concentrate on health promotion and service recipient satisfaction by guaranteeing the congruence of customer demands and service offered characteristics. Consumers want services from firms that are accountable and market-oriented, as well as customer-friendly. Additionally, the customer is now perceived differently, as a hybrid of the conventional patient and the contemporary consumer, with much greater information about the healthcare system, an openness to innovation, and an active participation in determining diagnosis, treatment, and health improvement. This research uses a narrative review approach, with many articles on the same problem. Articles are taken from a database from Scopus, Science Direct, ProQuest, SpringerLink, Google Scholar, Nature, JSTOR, and Emerald Insight with a total of 23 articles used. The purpose of this study is to determine whether management has a significant influence in decision making. decisions in hospitals with strategic support systems such as human resource development, program selection, marketing, and facility growth. Abstrak: Pemasaran jasa kesehatan merupakan strategi terpadu yang terdiri dari konsep-konsep pemasaran berdasarkan teknik ilmiah yang terutama berkonsentrasi pada promosi kesehatan dan kepuasan penerima layanan dengan menjamin kesesuaian permintaan pelanggan dan karakteristik layanan yang ditawarkan. Konsumen menginginkan layanan dari perusahaan yang akuntabel dan berorientasi pasar, serta ramah pelanggan. Selain itu, pelanggan sekarang dianggap berbeda, sebagai hibrida dari pasien konvensional dan konsumen kontemporer, dengan informasi yang jauh lebih besar tentang sistem perawatan kesehatan, keterbukaan terhadap inovasi, dan partisipasi aktif dalam menentukan diagnosis, pengobatan, dan peningkatan kesehatan. Penelitian ini menggunakan pendekatan narrative review, dengan banyak artikel tentang masalah yang sama. Artikel diambil dari database Scopus, Science Direct, ProQuest, SpringerLink, Google Scholar, Nature, JSTOR, dan Emerald Insight dengan total 23 artikel yang digunakan. Tujuan dari penelitian ini adalah untuk mengetahui apakah manajemen memiliki pengaruh yang signifikan dalam pengambilan keputusan. keputusan di rumah sakit dengan sistem pendukung strategis seperti pengembangan sumber daya manusia, pemilihan program, pemasaran, dan pertumbuhan fasilitas.